Extensor tendon repair an overview - Mansoor Bin Fayed; Mohammed Azmathullah (Al Ameen Medical College, 2015)
The incidence of extensor injuries is more than that of flexor tendon injuries. This is to a great extent because of the extensors being superficially placed and covered by skin and subcutaneous tissue over the distal part of the upper extremity. Thus they are more vulnerable to blunt and sharp trauma, the proximal and distal forearm present with laceration and cut with sharp weapon. Extensor tendon injuries are often taken lightly by many, repairs being taken-up at the ER. Repair is done in or if the retrieval of tendon ends is difficult or the wound is complicated with associated injuries such as fractures or in cases of tendon retraction. Delayed primary repair can be undertaken from 7-10 days. Assessment of the injured finger has to be very meticulous. Extension of finger is brought about by the interossei and lumbricals which are the short muscles of the hand. They extend the proximal interphalangeal joints and distal interphalangeal joints and flex metacarpophalangeal joint, these intrinsic muscles are innervated by the ulnar and median nerves. The long extensors are innervated by the radial nerve, they primarily extend the metacarpophalangeal joints and also interphalangeal joints. In cases of injury the intrinsic system may compensate for an extensor deficit. Closed injuries of zone I may be managed by splinting of the distal interphalangeal joints and open injuries in the zone I and II can be treated with tenodermodesis. Proximal interphalangeal joints and distal interphalangeal joints are immobilized in zone 3 and 4. Metacarpophalangeal joint is immobilized in full extension and the wrist in 10o extension.